Design of logistics indicators for monitoring the COVID-19 vaccination process in Colombia - Nubia Velasco; Andrea Herrera; Johanna Trujillo-Diaz; Ciro-Alberto Amaya; Catalina González-Uribe; Estefania Hernandez (BMC, 2024)
Abstract Background The vaccine supply chain (VSC) integrates all activities from production to dispensing, characterized by complexity and low responsiveness. This study aims to define key performance indicators (KPIs) to evaluate the logistic and operational performance during the COVID-19 National Vaccination Plan in Colombia. Methods This study employed the design science research (DSR) methodology to develop a dashboard for monitoring COVID-19 vaccination progress. DSR is a problem-solving paradigm focused on conceiving, testing, and evaluating artifacts to tackle specific challenges. The dashboard integrated a set of Key Performance Indicators (KPIs) that incorporated three dimensions: epidemiological, humanitarian, and logistical. Both, the dashboard and the KPIs underwent validation through three iterative DSR cycles, in collaboration with both private and public health stakeholders. Results A set of 38 validated KPIs, grouped into eight categories, was consolidated into an online dashboard. This tool enabled real-time tracking of the National Vaccination Plan at both national and departmental levels, providing stakeholders with a comprehensive view of the vaccine supply chain. It also allowed for the assessment and comparison of the execution and effectiveness of public policies. Conclusions These KPIs supported decision-making from a logistical standpoint, enhancing the planning, preparation, and continuous improvement of mass vaccination processes, thereby increasing their potential impact even further.